2022
DOI: 10.3390/biomimetics7040172
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Biophysical Interaction of DNA/BSA, Equilibrium and Stopped-Flow Kinetic Studies, and Biological Evaluation of bis(2-Picolyl)amine-Based Nickel(II) Complex

Abstract: Reaction of bis(2-picolyl)amine (BPA) with Ni(II) salt yielded [(BPA)NiCl2(H2O)] (NiBPA). The Ni(II) in NiBPA bound to a BPA ligand, two chloride, and one aqua ligands. Because most medications inhibit biological processes by binding to a specific protein, the stopped-flow technique was used to investigate DNA/protein binding in-vitro, and a mechanism was proposed. NiBPA binds to DNA/protein more strongly than BPA via a static quenching mechanism. Using the stopped-flow technique, a mechanism was proposed. BSA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…The hydrogen bond acceptor sites of the DNA phosphate group in combination with DNA polymerase can thus be mimicked using the triazole template strand [ 53 ] or TSPH 2 , and this will have an effect on DNA bending, rigidity, and recognition. In a previous study [ 41 ], the docking results showed that BSA-[RuNOTSP] + with binding affinity (−7.27 kcal/mol) and BSA-TSPH 2 with binding affinity (−8.05 kcal/mol) are located in subdomain IA and it has recently been reported as a possible binding site for drugs on BSA [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrogen bond acceptor sites of the DNA phosphate group in combination with DNA polymerase can thus be mimicked using the triazole template strand [ 53 ] or TSPH 2 , and this will have an effect on DNA bending, rigidity, and recognition. In a previous study [ 41 ], the docking results showed that BSA-[RuNOTSP] + with binding affinity (−7.27 kcal/mol) and BSA-TSPH 2 with binding affinity (−8.05 kcal/mol) are located in subdomain IA and it has recently been reported as a possible binding site for drugs on BSA [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…As it is expected that the drug interaction will happen so quickly, a fast kinetic method is needed to find transient intermediates in the interaction pathway. We employed the stopped-flow technique in earlier studies [ 37 , 38 , 39 , 40 , 41 ], in which sample and reagent solutions were quickly mixed, and measurements were taken almost immediately after mixing. Using this technique, it was found that other factors, such as drug affinity and the kinetic stability of the DNA/protein–drug complex, are also essential for biological activity when examining how various drugs interacted with DNA and proteins.…”
Section: Introductionmentioning
confidence: 99%
“…We used a stopped-flow technique for carrying out a kinetic investigation of the binding process because it is thought that DNA/protein–drug interaction is a fast step. This method aids in identifying the kinetic characteristics of the phases leading to intermediate species and ultimately obtaining an interaction mechanism [ 41 , 42 , 43 , 44 , 45 , 46 ], The geometrically optimized parameters (bond lengths, bond angles, and dihedral angles) were computed using DFT/B3LYP theory on the chitosan moiety and HCQ. Docking simulation will be used in order to confirm the spectroscopic results of the binding of HCQ to the BSA structure and the formation of the HCQ–BSA complex.…”
Section: Introductionmentioning
confidence: 99%